2017
DOI: 10.1186/s40673-017-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic analysis of spinocerebellar ataxia type 7 (SCA7) in Zambian families

Abstract: BackgroundTo date, 43 types of Spinocerebellar Ataxias (SCAs) have been identified. A subset of the SCAs are caused by the pathogenic expansion of a CAG repeat tract within the corresponding gene. Ethnic and geographic differences are evident in the prevalence of the autosomal dominant SCAs. Few descriptions of the clinical phenotype and molecular genetics of the SCAs are available from the African continent. Established studies mostly concern the South African populations, where there is a high frequency of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Clinically, visual disturbances may precede other symptoms in SCA7, and multimodal imaging may facilitate the observation of retinal change and is bene cial to detect early lesions of ATXN7-related retinopathy. The retinal phenotype in our patients indicating a cone-rod dystrophy generally agrees with previous reports 1,[8][9][10][11] . In our cohort, all the patients complained of progressive bilateral visual loss, and most cases reported visual disturbance earlier than dyskinesia or dysarthria.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Clinically, visual disturbances may precede other symptoms in SCA7, and multimodal imaging may facilitate the observation of retinal change and is bene cial to detect early lesions of ATXN7-related retinopathy. The retinal phenotype in our patients indicating a cone-rod dystrophy generally agrees with previous reports 1,[8][9][10][11] . In our cohort, all the patients complained of progressive bilateral visual loss, and most cases reported visual disturbance earlier than dyskinesia or dysarthria.…”
Section: Discussionsupporting
confidence: 92%
“…Presenting visual symptoms may include photophobia, dyschromatopsia, decreased vision and hemeralopia 7 . The appearance of the fundus in SCA7 is variable, and the reported phenotypes range from normal appearance, occult macular dystrophy (OMD), macular dystrophy and cone-rod dystrophy 1,[8][9][10][11] . Ocular motor abnormalities may include slowed saccades, saccadic pursuits, saccadic dysmetria and gaze-evoked nystagmus 7 , which are relatively non-speci c for olivopontocerebellar atrophies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the first Moroccan family with SCA7 in the South of Morocco. There are a few SCA7 reports from Algeria, Angola, Cape Verde, Liberia, Mali, Morocco, South Africa, Tunisia and Zambia [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of SCA6 patients did not find cognitive abnormalities compared to healthy controls [44]. A series of 19 African patients with SCA7 described dementia in almost half of affected cases, particularly as a late feature [45]. A longitudinal study, however, found only minor cognitive changes in SCA7, comparable to SCA6 [46].…”
Section: Introductionmentioning
confidence: 99%